Korelasi Penguasaan Kosakata dengan Keterampilan Menulis Teks Berita Siswa Kelas VIII SMP Kartika Pekanbaru - Lestari, Febby Nabila; Septyanti, Elvrin; Zulhafizh, Zulhafizh (Program Studi Pendidikan Bahasa dan Sastra Indonesia FKIP Universitas Islam Riau, 2023)
This study aims to determine the relationship between vocabulary skills and news text writing skills. The study involved a sample of class VIII students at SMP Kartika 1-5 Pekanbaru. The research is quantitative, using correlation as the method. The data used consists of objective tests and performance evaluations. The results of the data analysis indicate that the student's vocabulary mastery level was classified as good, with an average of 74.636, while their ability to write news texts was also classified as good, with an average of 77.634. The data analysis reveals a significant relationship between vocabulary skills and news text writing skills. This relationship is evident from the correlation coefficient value tested using the Pearson product-moment correlation formula. The calculations demonstrate that the value of the count is 0.962, which is greater than r table (0.2681), indicating a genuine correlation between variable X and variable Y. According to the interpretation table for correlation levels, this falls into the high category, within the scale of 0.80-1.00. Hypothesis testing using the t-test and f-test, with a 95% confidence level and degrees of freedom (dk) = n-2, yielded values of 4.761 > 1.675 and 653.343 > 4.02, respectively. Therefore, H0 is rejected, and H1 is accepted, as the hypothesis testing results prove a significant positive correlation of 96.2% between vocabulary skills and news text writing skills among class VIII students of SMP Kartika 1-5 Pekanbaru. Keywords: ability, vocabulary, writing news text.